Impact of novel SNPs identified in Cynara cardunculus genes on functionality of proteins regulating phenylpropanoid pathway and their association with biological activities. (December 2017) - Ferro, Ana; Ramos, Patrícia; Guerreiro, Olinda; Jerónimo, Eliana; Pires, Inês; Capel, Carmen; Capel, Juan; Lozano, Rafael; Duarte, Maria; Oliveira, M.; Gonçalves, Sónia
Abstract Background Cynara cardunculus L. offers a natural source of phenolic compounds with the predominant molecule being chlorogenic acid. Chlorogenic acid is gaining interest due to its involvement in various biological properties such as, antibacterial, antifungal, antioxidant, hepatoprotective, and anticarcinogenic activities. Results In this work we screened aCynara cardunculus collection for new allelic variants in key genes involved in the chlorogenic acid biosynthesis pathway. The target genes encodep -coumaroyl ester 3′-hydroxylase (C3′H) and hydroxycinnamoyl-CoA: quinate hydroxycinnamoyl transferase (HQT), both participating in the synthesis of chlorogenic acid. Using high-resolution melting, the C3′H gene proved to be highly conserved with only 4 haplotypes while, for HQT, 17 haplotypes were identifiedde novo . The putative influence of the identified polymorphisms in C3′H and HQT proteins was further evaluated using bioinformatics tools. We could identify some polymorphisms that may lead to protein conformational changes. Chlorogenic acid content, antioxidant and antithrombin activities were also evaluated inCc leaf extracts and an association analysis was performed to assess a putative correlation between these traits and the identified polymorphisms. Conclusion In this work we identified allelic variants with putative impact on C3′H and HQT proteins which are significantly associated with chlorogenic acid content and antioxidant activity. Further study of these alleles should be explored to assess putative relevance as genetic markers correlating withCynara cardunculus biological properties with further confirmation by functional analysis.